2018
DOI: 10.1039/c8ra06798h
|View full text |Cite
|
Sign up to set email alerts
|

Co-immobilised 7α- and 7β-HSDH as recyclable biocatalyst: high-performance production of TUDCA from waste chicken bile

Abstract: Chicken gallbladder has long been considered to be worthless and discarded as waste. The main composition of chicken bile is taurochenodeoxycholic acid (TCDCA), which is the isomeride of tauroursodeoxycholic acid (TUDCA). TUDCA has been effectively used for treatment of many diseases. In this paper, 7a-and 7bhydroxysteroid dehydrogenases (HSDH) were co-immobilised on modified chitosan microspheres, and used as recyclable biocatalyst for the catalysis of chicken bile. The catalytic reaction reached equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Furthermore, from the change of peak area, we can see that there was almost no conversion of TCDCA when the concentration of bilirubin in buffer was 0.8 mM. Except for bilirubin, the experiments showed that Cu 2+ and Ca 2+ also have some inhibition to 7α-and 7β-HSDH [22].…”
Section: The Effect Of Bilirubin On Enzymatic Reactionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, from the change of peak area, we can see that there was almost no conversion of TCDCA when the concentration of bilirubin in buffer was 0.8 mM. Except for bilirubin, the experiments showed that Cu 2+ and Ca 2+ also have some inhibition to 7α-and 7β-HSDH [22].…”
Section: The Effect Of Bilirubin On Enzymatic Reactionmentioning
confidence: 87%
“…Furthermore, both free enzymes and immobilized enzymes are suitable for the two steps catalytic reactions. Besides, the waste chicken bile is rich in TCDCA, the sufficient source of substrate can be ensured [22]. Bilirubin is one of the main components of waste chicken bile, from which substrate TCDCA is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study, 7α-and 7β-HSDHs were co-immobilized on modified chitosan microspheres and used as recyclable biocatalyst for the catalysis of chicken bile [22]. We found that the activities of 7α-and 7β-HSDHs were affected by bilirubin and Cu 2+ .…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, both free enzymes and immobilized enzymes are suitable for two-step catalytic reactions. The waste chicken bile is rich in TCDCA and a sufficient source of substrate can be ensured [22]. Bilirubin is one of the main components of waste chicken bile, from which substrate TCDCA is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…7α-HSDHs can catalyze the C-7 α-position hydroxyl dehydroxylation reaction of CA or CDCA and their taurine or glycine conjugates, such as TCA, TCDCA, glycocholic acid (GCA), and glycochenodeoxycholic acid (GCDCA) to form keto groups, then 7β-HSDHs catalyze the reduction of the keto group to β-OH, realizing the epimerization of 7-OH configuration inversion, and the coenzyme NADP(H) is added to realize the reaction cycle (Scheme 1) [10]. Ji et al pointed out that chicken bile powder could be selected as the substrate for biosynthesis of TUDCA owing to its high content of TCDCA (about 42.58%), turning waste into treasure [11,12]. However, chicken bile powder contains 4.74% TCA, and a new by-product TUCA could be produced, resulting in purification difficulties and lower production of TUDCA.…”
Section: Introductionmentioning
confidence: 99%